Anaplasma phagocytophilum-Borrelia burgdorferi Coinfection Enhances Chemokine, Cytokine, and Matrix Metalloprotease Expression by Human Brain Microvascular Endothelial Cells - Grab, Dennis J. (American Society for Microbiology (ASM), 2007)
Borrelia burgdorferi and Anaplasma phagocytophilum coinfect and are transmitted by Ixodes species ticks. Clinical indicators suggest that A. phagocytophilum coinfection contributes to the severity, dissemination, and, possibly, sequelae of Lyme disease. Previous in vitro studies showed that spirochete penetration through human brain microvascular endothelial cells of the blood-brain barrier is facilitated by endothelial cell-derived matrix metalloproteases (MMPs). A. phagocytophilum-infected neutrophils continuously release MMPs and other vasoactive biomediators. We examined B. burgdorferi infection of brain microvascular barriers during A. phagocytophilum coinfection and showed that coinfection enhanced reductions in transendothelial electrical resistance and enhanced or synergistically increased production of MMPs (MMP-1, -3, -7, -8, and -9), cytokines (interleukin 6 [IL-6], IL-10, and tumor necrosis factor alpha), and chemokines (IL-8 and macrophage inflammatory protein 1α) known to affect vascular permeability and inflammatory responses.